A retrospective review of surgical site infection following caesarean section at Mowbray Maternity Hospital - Sonntag, Kim (Department of Obstetrics and Gynaecology, 2017)
Introduction: Pregnancy related sepsis is a major cause of maternal mortality and morbidity in South Africa. Caesarean section (CS) is the most important risk factor in the development of puerperal infection, and surgical site infection (SSI) after CS increases maternal morbidity as well as medical costs. Mowbray Maternity Hospital (MMH), is a secondary level, public maternity hospital. The caesarean section rate at MMH has increased considerably over the last fifteen years, and the perception has been that there have been increasing numbers of patients developing SSI post-CS. This study was designed to look more closely at the incidence of SSI and to describe the patients identified with SSI. Methods: This was a retrospective observational study. Cases of severe SSI, as defined by the Centres for Disease Control and Prevention (CDC), following CS at MMH from December 2011 to December 2014 were identified. Following ethical approval, patient records were sourced, data collected and analysed using Stata and Statistica. Results: In the 3-year study period, 14982 CS were performed with 98 patients identified with severe SSI. Folders were retrieved for 96 patients, with 2 patients' folders missing and 29 patients with a missing maternity case record (MCR). The overall incidence of severe SSI was 0.65%, with an incidence of 0.88% in Year 1, 0.90 in Year 2 and 0.70 in Year 3. Of the cases, 79 (80.6%) had been in labour, 16 (16.3%) patients had had prolonged rupture of membranes (PROM) and 32 (32.7%) had prolonged labour, with a median of 5 vaginal examinations. An emergency CS was performed in 90 (91.8%) patients, 7 (7.2%) had an elective CS and 1 (1.0%) patient had this data missing. Deep incisional SSI was diagnosed in 74 (75.5%) patients and 24 (24.5%) patients were identified with organ/space SSI. Intravenous (IV) antibiotics was the main treatment in all 96 cases, with 23 (23.5%) patients requiring a wound debridement, 17 (17.2%) a laparotomy, which proceeded to a hysterectomy in 12 (12.3%) patients. In the majority of cases, no organism was cultured, Whereas multiple organisms were cultured in 16 cases, of which 12 were identified as MRSA, and 18 as Klebsiella pneumoniae. There were no maternal deaths or Intensive Care Unit (ICU) admissions. Discussion and Conclusion: The incidence of severe SSI is in keeping with other institutions, with the lowest incidence being found in Year 3, which may be explained by the change in referral population and/ or the full implementation of the Best Care Always (BCA) bundles of care. Of the 98 patients with severe SSI, 80.6% had been in labour, 32.7% had prolonged labour and 91.8% had an emergency CS performed. These are all factors which are known to increase the likelihood for development of post-CS SSI.